Efficient production and evaluation of lignocellulolytic enzymes using a constitutive protein expression system in Penicillium oxalicum. (1st June 2015) - Hu, Yibo; Xue, Haizhao; Liu, Guodong; Song, Xin; Qu, Yinbo
Abstract: Native lignocellulolytic enzyme systems secreted by filamentous fungi can be further optimized by protein engineering or supplementation of exogenous enzyme components. We developed a protein production and evaluation system in cellulase-producing fungus Penicillium oxalicum . First, by deleting the major amylase gene amy15A, a strain Δ15A producing few extracellular proteins on starch was constructed. Then, three lignocellulolytic enzymes (BGL4, Xyn10B, and Cel12A) with originally low expression levels were successfully expressed with selected constitutive promoters in strain Δ15A. BGL4 and Cel12A overexpression resulted in increased specific filter paper activity (FPA), while the overexpression of Xyn10B improved volumetric FPA but not specific FPA. By switching the culture medium, this platform is convenient to produce originally low-expressed lignocellulolytic enzymes in relatively high purities on starch and to evaluate the effect of their supplementation on the performance of a complex cellulase system on cellulose.